Validation of definitions for structural lesions detected by magnetic resonance imaging in the spine of patients with spondyloarthritis - Praveena Chiowchanwisawakit (2018)
Objective. Assessment of structural features of spondyloarthritis (SpA) on magnetic resonance imaging (MRI) has proven to be no more reliable than plain radiography, which may reflect a lack of standardization and application of rigorous definitions. The Canada-Denmark MRI Working Group has developed a comprehensive list of definitions for the structural MRI changes in the spine of patients with SpA. We conducted a systematic evaluation of the frequency and reliability of detection of structural lesions. Methods. Chronic lesions were independently recorded dichotomously (present/absent) from lower C2 to the upper sacrum on T1-weighted MRI scans of 20 patients with ankylosing spondylitis by 4 readers. Prior to the exercise, a series of reference images was developed in which structural lesions were assigned by consensus. We tested a method for scoring new bone formation based on assigning a score of 2 for a bone spur and a score of 6 for intervertebral ankylosis [Canada-Denmark Spur and Ankylosis score (CanDen SAS)]. Results. Focal fat infiltration and non-corner vertebral endplate erosions were observed in the majority of patients and were reliably detected. Vertebral corner erosions were not reliably detected. New bone lesions were also detected in almost all patients, and intervertebral ankylosis was detected with good reliability. Bone spurs were not reliably detected. The CanDen SAS demonstrated excellent interobserver reliability (ICC = 0.93) across 4 readers. Conclusion. Definitions for focal fat infiltration, non-corner vertebral erosions, and intervertebral ankylosis function well as regards reliability. Despite rigorous standardization of definitions, substantial calibration is required for vertebral corner erosions and bone spurs. The Journal of Rheumatology Copyright © 2009. All rights reserved.